Liquid Biopsy of Bile based on Targeted Mass Spectrometry for the Diagnosis of Malignant Biliary Strictures. Issue 1 (23rd October 2020) - Adrait, Annie; Dumonceau, Jean‐Marc; Delhaye, Myriam; Annessi‐Ramseyer, Isabelle; Frossard, Jean‐Louis; Couté, Yohann; Farina, Annarita
Abstract : Bile holds biomarkers of malignant biliary strictures (MBS) but is unsuited for automated analyzers used in routine diagnostic laboratories. Selected reaction monitoring (SRM) is a flexible high‐throughput analytical approach based on targeted mass spectrometry (MS) already implemented in clinical settings. We tested the hypothesis that SRM could be used to quantify cancer biomarkers in human bile. An SRM‐based assay was developed to simultaneously quantify up to 37 peptides from 13 bile proteins in a developmental cohort of 15 patients (MBS, n = 8; benign biliary stricture or obstruction (BBS), n = 7). The most reliable biomarkers were then absolutely quantified by SRM in a verification cohort of 67 patients (MBS, n = 37; BBS, n = 30). The diagnostic performances of single and combined biomarkers were assessed. In the developmental cohort, SRM‐based analysis revealed six protein biomarkers with significantly higher peptide ratios (endogenous vs. standard) in bile from MBS vs. BBS. In the verification cohort, five of these biomarkers proved good diagnostic ability (individual receiver operating characteristic‐area under the receiver operating characteristic curve (ROC‐AUC) up to 0.889, accuracies from 67.8% to 83.1%). Combining bile biomarkers and serum CA19‐9 in 2 panels allowed differentiating MBS from BBS with up to 0.929 ROC‐AUC and 89.8% accuracy. In this study, a newly developed SRM‐based assay proved able to simultaneously quantify multiple biomarkers in bile samples. The combination of bile biomarkers with serum CA19‐9 was highly accurate for the diagnosis of MBS. Liquid biopsy of bile based on targeted MS is eligible to support MBS diagnosis in clinical practice.